FACTORS INFLUENCING THE FORMATION OF GENDER CULTURE IN SOCIETY (Modern education and development, 2025)
The formation of gender culture in society is a complex and dynamic process influenced by various social, cultural, economic, and educational factors. This article explores the key elements that contribute to the development of gender culture, including the role of family, education systems, media, and government policy. Special attention is given to how traditional norms and modern values interact in shaping gender perceptions. The study emphasizes the importance of promoting gender equality and awareness through comprehensive cultural and educational initiatives to foster a more inclusive and equitable society.